Statistical Analysis of Conceptual Metaphors of Causation in Mulla Sadra’s Al-Shawahid Al-Rubūbīyyah - Vahid Khademzadeh; Kokab Darabi (Pizhūhish/hā-yi Falsafī- Kalāmī, 2021)
The theory of conceptual metaphor claims that abstract concepts are understood by concrete and less abstract concepts. Conceptual metaphors map the conceptual structure of the source domain over the conceptual structure of the target domain. In this view, a conceptual metaphor is an intrinsic component of human thought, and the appearance of metaphors in language is only a sign of their existence in human thought.Lakoff and Johnson introduce causation as one of the important abstract concepts that are understood and described by various conceptual metaphors. Causation is conceptualized both in ordinary and everyday language and in scientific and specialized texts through single cognitive mechanisms.Mulla Sadra is one of the greatest Muslim philosophers and Al-Shawahid Al-Rubūbīyyah is one of his most important philosophical books. In the framework of the conceptual metaphor theory, this study has analyzed the various terms used to describe causation in Al-Shawahid Al-Rubūbīyyah written by Mulla Sadra. The most important conceptual metaphors that are used in this book to describe causation have been extracted. Each of these metaphors emerges through the derivatives of one or more lexical roots in this book.In this study, Mulla Sadra’s use of metaphors is quantified based on statistical methods. By calculating the frequency of metaphoric usage of all the words that describe causation related to a metaphor, the frequency of that metaphor is extracted in the book.The “Causation is motion out” metaphor (306) emerges through the derivations of «ṣ-d-r» (49), «n-sh-’» (124), «f-y-ḍ» (82), «r-sh-ḥ» (2), «j-l-w » (18) and «ẓ-h-r» (31) roots. The “Causation is making an impression” metaphor (112) is revealed by the derivations of «‘- th-r» (112) root. The “Cause is source” metaphor (120) is related to the derivations of «b-d-’» (120) root. The “Causation is being basis” metaphor (156) is represented by the derivations of «q-w-m» (156) root. The “Causation is making” metaphor (117) includes the derivations of «j-‘-l» (107) and «ṣ-n-‘» (10) roots. The “Causation is transfer of possessions” metaphor (61) is revealed by the derivations of «‘-ṭ-w» (14), «w-h-b» (15) and «f-y-d» (32) roots.The frequency of metaphorical use of each of the lexical roots and related conceptual metaphors in this book is shown by numbers in parentheses.According to the statistical results, the “causation is motion out” metaphor has the highest frequency and the “causation is transfer of possessions” metaphor has the lowest frequency in the book.Statistical differences between the two metaphors can find a philosophical explanation. According to the “causation is motion out” metaphor, the cause is like a boiling and luminous fountain whose effects are considered as its manifestations and overflowing water. Such an image of causation is in great harmony with Mulla Sadra’s philosophical system. But in the “causation is transfer of possessions” metaphor, there is a clear distinction between cause and effect, and causation is considered as a kind of forced movement caused by the application of force. Such an image of causation is less compatible with Mulla Sadra’s philosophical system.